2020
DOI: 10.1590/0074-02760200215
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of Latin American-Mediterranean family of Mycobacterium tuberculosis clinical strains from Kazakhstan

Abstract: The human-adapted strains of the Mycobacterium tuberculosis complex (MTBC) comprise seven phylogenetic lineages originally associated with their geographical distribution. Here, we report the genomes of three drug-resistant clinical isolates of the Latin American-Mediterranean (LAM) family collected in Kazakhstan. We utilised whole-genome sequencing to study the distribution and drug resistance of these isolates. Phylogenetic analysis grouped the genomes described in this study with the sequences from Russia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Among the rifampicin-resistant isolates, the LAM genotype was associated with the His526Leu mutation of the rpoB gene (p < 0.0001; OR = 141.3333; 95%CI: 15.9020-1256.1369). This mutation of the rpoB gene was also identified in the genomes of drug-resistant LAM isolates (66.7%; 2/3) from Kazakhstan [34].…”
Section: Discussionmentioning
confidence: 70%
“…Among the rifampicin-resistant isolates, the LAM genotype was associated with the His526Leu mutation of the rpoB gene (p < 0.0001; OR = 141.3333; 95%CI: 15.9020-1256.1369). This mutation of the rpoB gene was also identified in the genomes of drug-resistant LAM isolates (66.7%; 2/3) from Kazakhstan [34].…”
Section: Discussionmentioning
confidence: 70%
“…Only some publications relate to preliminary data and reported several genome sequences of DR (including one XDR and several MDR) clinical isolates of M. tuberculosis isolated in Kazakhstan performed by using a next-generation sequencing platform [ 24 , 25 , 26 , 27 , 28 , 29 ]. Drafts of complete genome sequences of two Kazakhstani isolates [ 24 ] and one isolate with extensive drug resistance [ 26 , 27 ] were published by our group.…”
Section: Discussionmentioning
confidence: 99%
“…Drug resistance mutations in the genome were reported as a part of the study of the mechanisms of Reversion of Antibiotic Resistance in MDR Mycobacterium tuberculosis induced by a Nanomolecular Iodine-Containing Complex FS-1 [ 25 ]. The genomes of three drug-resistant clinical isolates of the Latin American-Mediterranean (LAM) family collected in Kazakhstan were reported by Tarlykov et al [ 28 ]. A last study of ours concentrated on WGS MDR-TB isolates from Kazakhstan [ 29 ] and identified Lineage 2 East-Asia (Beijing) as a major contributor to the genetic diversity of MTB in the region.…”
Section: Discussionmentioning
confidence: 99%
“…Only a handful of regional studies have used the WGS approach to characterize the MTBC population in Kazakhstan. The sample size in these studies usually does not exceed 10 isolates due to budget constraints and/or lack of funding [8,9,11,12,28,29]. As a result, WGS technology has not been widely adopted in Kazakhstan in clinical or other settings.…”
Section: Discussionmentioning
confidence: 99%
“…A PubMed search using the terms "whole-genome sequencing", "Kazakhstan", and "tuberculosis" found only six publications, describing a total of 97 Sequence Read Archive (SRA) whole-genome sequences of local Mtb isolates. This suggests that the use of WGS in TB research and surveillance is not yet widespread in Kazakhstan [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%